Methylenetetrahydrofolate reductase and methionine synthase reductase gene polymorphisms in Iranian ventricular septal defect subjects - Pishva, Seyyed Reza (2013)
Congenital heart defects (CHD) are among the most pervasive congenital anomalies globally, occurring in an average of one in hundred living newborn babies. This occurrence of CHD is related to the relative frequency of ventricular septal defects (VSDs), which is the most common type of CHD. Heart defects at birth occur as an insular malformation, but are also linked with other anomalies or occur as part of a syndrome. There are vivid multifactorial causes for CHD in which both genetic and environmental risk factors are consequential in the development of CHD. Single nucleotide polymorphisms (SNPs) are the predisposing genetic risk factors for the contribution to major diseases. Genes involved in homocysteine/folate metabolism may play an important role in CHDs. Methionine synthase reductase (MTRR) and Methylenetetrahydrofolate Reductase (MTHFR) are one of the key regulatory enzymes involved in the metabolic pathway of homocysteine. In this study, we determined the association of A66G and C524T polymorphisms of the MTRR gene and C677T polymorphism of the MTHFR gene with Iranian VSD subjects. A total of 123 children with VSDs and 125 healthy children were included in this study. Buccal cells were collected from subjects using cytology brush according to the inclusion and exclusion criteria. The PCR was carried out to amplify the MTRR and MTHFR genes. The amplified PCR products of MTHFR C677T, MTRR C524T and MTRR A66G gene polymorphisms were digested with Hinf1, XHO1and Nde1enzymes respectively using Restriction Fragment Length Polymorphism method. The distribution of genotypic and allelic frequency of polymorphisms was obtained using Chi square test. The genotype frequencies of CC,CT and TT of MTRR gene among cases were 43.1%, 40.7% and 16.3% respectively compared to 52.8%, 43.2% and 4.0% respectively among controls. For the MTRR A66G gene polymorphism, the genotypes frequencies of AA, AG and GG among cases were 33.3%, 43.9% and 22.8% respectively, while the frequencies were 49.6%, 42.4% and 8.0% among control subjects. The frequencies for CC and CT genotypes of the MTHFR gene were 51.2% and 48.8%, respectively, in VSD patients, and in control subjects were 56.8% and 43.2% respectively. Significant differences in the genotypic and allelic frequency distributions of both MTRR C524T and MTRR A66G polymorphisms between cases and controls were observed (p<0.05) whereas for MTHFR C677T polymorphism between cases and controls there was no significant association of neither genotypic nor allelic frequencies (p>0.05). In conclusion, the association of C524T and A66G gene polymorphisms of MTRR gene is considered as risk factors for the development of VSD in Iranian subjects.